Effect of water absorption on some mechanical and physical properties of epoxy/polyurethane blend reinforced with nano silica powder - Salih, Rana M. (Iraqi Journal of Physics, 2019)
The aim of this work is to evaluate some mechanical and physicalproperties (i.e. the impact strength, hardness, flexural strength,thermal conductivity and diffusion coefficient) of(epoxy/polyurethane) blend reinforced with nano silica powder (2%wt.). Hand lay-up technique was used to manufacture the compositeand a magnetic stirrer for blending the components. Results showedthat water had affected the bending flexural strength and hardness,while impact strength increased and thermal conductivity decreased.In addition to the above mentioned tests, the diffusion coefficientwas calculated using Fick’s 2nd law.